Estudo de concreto com poliestireno expandido reciclado - Carvalho, Carlos Henrique Rezende (2017)
The lightweight concrete obtained with the addition of expanded polystyrene (EPS) particles is designated concrete with EPS. The aim of this paper is investigate the properties of concrete with the addition of two different EPS contents on structural panels. Due to its low density and large scale manufacturing, there is a large amount of waste generated the use of EPS produces a large quantity of not recycled waste. In regard to help preserve and protect the environment, particular attention will be paid on performance of the concrete with the addition of EPS in beads and recycled EPS. Five mixtures were prepared: the first one was for control purposes (reference mixture) and had no addition of EPS and the others were prepared with two different percentages of EPS in beads and recycled EPS, trying to evaluate the influence of them on the properties of the mixture. Compression strength behavior, specific mass, voids content, immersion and capillarity absorption were the developed tests, performed using small cubic wooden molds covered with slabs of the mixtures to measure the heat flow through the samples and the temperature inside the molds. It was verified that the compressive strength of the mixture with the addition of EPS presented lower rates (34 to 50%) in relation to the reference concrete (without the addition of EPS). Best result was obtained on the mixture with lower content of EPS in beads. Regarding physical properties, the reference mixture achieved the lowest absorption rate and voids content while the mixture with highest content of EPS in beads had the highest rates for these properties. However, regarding the capillarity absorption, the reference mixture had the worst performance, while the concretes with EPS (especially the one with highest content of EPS in beads) performed better, reducing the capillarity absorption. Finally, on thermal tests all mixtures with EPS presented better results than the reference concrete, decreasing levels of temperature achieved by the slabs and inside the compartments and slower increasing rate of temperature, mainly the mixture with highest content of recycled EPS. Conclusions were that the replacement of EPS in beads by recycled, due to proximity in the results achieved, is conceivable, but further studies must be carried out in order to improve some of mixture properties for building and construction industry use (structural panels) such as compressive strength behavior